Emergency Cardiology - Ratib, Karim (Taylor & Francis, 2011)
This fully revised and updated second edition offers practical advice on the diagnosis and management of acute cardiac conditions. Throughout the book, the authors employ an evidence-based approach to clinical practice and provide detailed guidance for day-to-day practice in a wider variety of settings-from the emergency department to intensive care and the cardiac ward. Authored by four cardiologists with extensive experience in the emergency setting, it includes the results of the most groundbreaking clinical trials. Topics include arrhythmias, acute aortic syndromes, pericarditis, and cardiac trauma.